2015
DOI: 10.1021/acs.energyfuels.5b01398
|View full text |Cite
|
Sign up to set email alerts
|

VOCs Emissions from Multiple Wood Pellet Types and Concentrations in Indoor Air

Abstract: Wood pellet storage safety is an important aspect for implementing woody biomass as a renewable energy source. When wood pellets are stored indoors in large quantities (tons) in poorly ventilated spaces in buildings, such as in basements, off-gassing of volatile organic compounds (VOCs) can significantly affect indoor air quality. To determine the emission rates and potential impact of VOC emissions, a series of laboratory and field measurements were conducted using softwood, hardwood, and blended wood pellets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 27 publications
2
30
0
Order By: Relevance
“…Off-gassing of home construction materials is a known source of indoor BTEX exposure ( 14 , 60 , 61 ). The observed association between reported home construction in the six months preceding blood collection and increasing blood benzene level is supported by this.…”
Section: Discussionmentioning
confidence: 99%
“…Off-gassing of home construction materials is a known source of indoor BTEX exposure ( 14 , 60 , 61 ). The observed association between reported home construction in the six months preceding blood collection and increasing blood benzene level is supported by this.…”
Section: Discussionmentioning
confidence: 99%
“…Aldehydes are the most abundant NMVOCs from pellet storage, in which hexanal accounts for 80% of emitted aldehydes. Other lab study also showed that the main NMVOCs including methanol, pentane, pentanal and hexanal were generated by the oxidation of stored pellets [38]. Temperature was in accord with the TVOC concentrations from stored WRC chips.…”
Section: Discussionmentioning
confidence: 65%
“…In confined space, CO concentrations are several orders of magnitude higher than the occupational exposure limits. Serious accidents in Europe have been reported in the past decade, as the CO concentration was found to be high with a range of 14 ppm to 155 ppm (v/v) in the pellet storage bins [38].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported the emission rates and the maximum concentrations of the gases reduce at lower temperatures [13]. Tumuluru et al concluded that the gas emissions from stored wood pellets increased exponentially with storage temperature.…”
Section: Introductionmentioning
confidence: 99%